The importance of IT in supporting roller hockey referees - Cadavez, I.; Oliveira, A. (Ireland International Conference on Education (IICE 2020), 2020)
Technology is increasingly present everyday life. All people are users of technology and the world of sports is no exception. Indeed, there is a strong need for tasks improvement, and, in sports practice, the implementation of technologically advanced tools is a reflection of the execution of that objective, as athletes, coaches, referees, or fans, are involved in that process. However, roller hockey, which is considered an old and traditional sport, is out of sync with this new reality. Thus, the main issue one may tackle is to evaluate the importance of technology according to the perceptions of the different stakeholders involved in the Roller Hockey sport. Using questionnaires, we intend to characterize the perceptions regarding available technologies and potential applications. In this paper, some results of this study (N = 227) are presented, in so that the potential for introducing information technologies to the referee role may be understood.